In silico-in vitro discovery of untargeted kinase–inhibitor interactions from kinase-targeted therapies: A case study on the cancer MAPK signaling pathway. (August 2018) - Meng, Li; Huang, Zhijun
Graphical abstract: Highlights: A noncognate interaction profile between MAPK kinases and approved inhibitors is created. An integration of in silico analysis and in vitro assay is used to characterize the profile. A number of putative MAPK–inhibitor pairs are identified. The Regorafenib is suggested as a potential noncognate inhibitor of p38α kinase. Abstract: Protein kinase inhibitors have been widely used as therapeutic agents to treat a variety of diseases, but many of them may cause off-target effects by unexpectedly targeting other noncognate kinases due to high conversion across the protein kinase family. The mitogen-activated protein kinase (MAPK) signaling pathway plays an essential role in tumorigenesis, which has been recognized as a high priority in the druggable target candidates of anticancer therapy. Here, we attempt to investigate the untargeted kinase–inhibitor interactions (UKIIs) of kinase-targeted therapies for the cancer MAPK signaling cascade via an integration of biomolecular modeling, cell viability assay and kinase inhibition analysis. A systematic kinase–inhibitor interaction profile is created for 28 FDA-approved kinase inhibitor drugs across 9 caner-related MAPK kinases. The created profile is analyzed at structural, energetic and dynamic levels and, consequently, totally 18 promising UKII pairs with high theoretical affinity are derived, from which the noncognate inhibitors Cabozantinib, Regorafenib and Crizotinib are selected to test their cytotoxic effects on human epithelial colorectal adenocarcinoma Caco-2 cell line and inhibition activity against the recombinant protein of human p38α kinase domain. The obtained results are compared with two cognate MAPK inhibitors JNK-IN-8 and BIRB796. As might be expected, the Regorafenib, Crizotinib and Cabozantinib exhibit high, moderate and low cytotoxicities, respectively. In addition, the Regorafenib is determined to have a potent p38α-inhibitory activity. This is basically in line with the test results of positive controls JNK-IN-8 and BIRB796 and can be well confirmed by computational modeling.